(untitled) (Revista Latino-Americana de Enfermagem, 2011)
This study develops a theoretical model concerning the experience of families of children with Down syndrome in preschool and school age. The frameworks used were Symbolic Interactionism and Grounded Theory. Semi-structured interviews were used as the instrument of investigation and ten families participated in the study. The Theoretical Model "Seeking the child's independence and autonomy through constant stimulation" was identified, which shows the family's efforts to enable the child to develop the best s/he can through stimulation in order to become less dependent in the future. This model can be used to facilitate interaction with the family and can be further expanded. Nurses should use spaces dedicated to care delivery to establish bonds with the family, and seek other spaces families frequent, to better meet their needs, since there are significant gaps in care and research addressing this population. Instead, they should be welcomed and seen as a partner in care delivery.